The Degree of Student Teachers Acquisition at Sultan Qaboos University in Skills of Teaching Arabic via A Virtual Micro-Teaching Lab Based on their Point of View (Journal Of Educational and Psychological Researches, 2023)
The study aims to investigate the degree of student teachers at Sultan Qaboos University acquired skills in teaching Arabic via a virtual micro-teaching lab, as well as to reveal the difficulties they faced and their development proposals. To do this, the researchers developed a questionnaire divided into four dimensions: planning, implementation, evaluation, andethical values for the teaching profession, in addition to two open-ended questions to identify difficulties and suggestions. It was administered to (30) student teachers. The results revealed that the average degree of student-teacher acquisition of skills was high in its four dimensions. It ranged between (39.2) to (82.2), while the overall average was (56.2).It also showed that the most difficulty faced by student teachers was in implementing classroom situations. It was (44%) represented in loss of direct communication with students, where the training suggestions got the highest percentage (9.46%). The research concluded with a set of recommendations,including continuing efforts in training student teachers on interactive applications for distance learning and increasing teaching lab hours, where student teachers can repeat practical applications